Humanitarian intervention by international non-governmental organizations by application to Amnesty International (Economic studies journal, 2020)
The organizations concerned with human rights are playing an important role in defending these rights in various parts of the world, especially in light of the recent developments witnessed by the international community, in an abstract manner without prejudice to a people, race, religion or any other factor that distinguishes between human beings.  This is the slogan to transparently address humanitarian violations in the international arena.  Humanitarian intervention in case of serious human rights violations is an exception from the original because the principle in international law is non-interference and preserving the sovereignty of states, given that state sovereignty is the most important principles and foundations on which general international law is based, and humanitarian intervention has emerged as a means to protect these rights and defend  Against the violations it is subjected to, until this method became a dominant feature in recent times after these rights and the ways of protecting them were strengthened in accordance with provisions in the United Nations Charter